Mechanism of action of HMGB1 in urologic malignancies - Li, Dandan; Lei, Xu; Zhao, Lanlan; Fu, Qingqing; Chen, Yao; Yang, Xiaorong (Frontiers in Oncology, 2025)
High mobility group protein 1 (HMGB1) is a highly conserved chromatin-associated protein that is widely found in eukaryotic cells. Studies have shown that HMGB1 plays an important role in the development and progression of urological malignancies. As a classical damage-associated molecular pattern (DAMP), HMGB1 usually acts as a DNA chaperone in the nucleus. In response to external stimuli, HMGB1 is actively secreted by immune cells and can also be passively released into the extracellular space from necrotic cells. By interacting with various signaling pathways and receptors, HMGB1 can induce immune system activation and participate in carcinogenesis, metastasis and angiogenesis. This review systematically summarizes the role of recent research progress of HMGB1 in carcinogenesis, progression, prognosis and potential clinical applications of different urological malignancies, providing reference for the diagnosis and treatment of urological malignancies.